2018
DOI: 10.1021/jacs.7b10334
|View full text |Cite
|
Sign up to set email alerts
|

Donor Engineering for NIR-II Molecular Fluorophores with Enhanced Fluorescent Performance

Abstract: Organic fluorophores have been widely used for biological imaging in the visible and the first near-infrared windows. However, their application in the second near-infrared window (NIR-II, 1000-1700 nm) is still limited mainly due to low fluorescence quantum yields (QYs). Here, we explore molecular engineering on the donor unit to develop high performance NIR-II fluorophores. The fluorophores are constructed by a shielding unit-donor(s)-acceptor-donor(s)-shielding unit structure. Thiophene is introduced as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
349
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 438 publications
(363 citation statements)
references
References 76 publications
2
349
1
Order By: Relevance
“…When the water fraction in THF/water mixture gradually elevates to above 60 %, the PL intensities of both TPE‐Ph‐B and TPE‐Th‐B tremendously increase due to the formation of aggregates resulting in RIM, showing representative AIE feature. For TPE‐ETh‐B, as the oxygen‐containing ETh group enhances the water‐solubility of the whole molecule, water cannot serve as a desirable poor solvent. As a result, dimethyl sulphoxide (DMSO)/toluene were used as the good/poor solvent pair.…”
Section: Resultsmentioning
confidence: 99%
“…When the water fraction in THF/water mixture gradually elevates to above 60 %, the PL intensities of both TPE‐Ph‐B and TPE‐Th‐B tremendously increase due to the formation of aggregates resulting in RIM, showing representative AIE feature. For TPE‐ETh‐B, as the oxygen‐containing ETh group enhances the water‐solubility of the whole molecule, water cannot serve as a desirable poor solvent. As a result, dimethyl sulphoxide (DMSO)/toluene were used as the good/poor solvent pair.…”
Section: Resultsmentioning
confidence: 99%
“…Further, dialkyl substituted fluorene is employed as a shielding unit to introduce into the central DAD core to prevent the interaction with water. These strategies open up new avenues for developing a series of high bright NIR‐II fluorophores, of which the optimized one displays fluorescence emission peaked at 1048 nm with a QY of 5.3% in water . Despite long side chains being capable of reducing intermolecular interactions, they are found to also trigger molecular motions in aggregates, whose nonradiative decay spoils fluorescence QY .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the shielding unit–donor–acceptor–donor–shielding unit (S‐D‐A‐D‐S) backbone, we developed a series of NIR‐II fluorophores by tuning the donor units and side chains on the shielding unit and identified a super bright D‐A‐D dye with high quantum yield (QY) of ≈6.0% in water. In vivo imaging studies showed that IR‐FD had high tumor retention . PbS/CdS core/shell quantum dots (QDs) with dense polymer coating were selected for NIR‐IIb imaging to visualize cancer‐associated sentinel LNs.…”
mentioning
confidence: 99%